How Do Meta-Organizations Reach Collective Action? A Comparative Study of Digital Transformation in Healthcare - Chienhung Chen; Chih-Yuan Wang; Zhao-Hong Cheng; Kune-Ping Shieh (Asia Pacific Journal of Health Management)
Objective: To investigate how meta-organizations and traditional hierarchical organizations differ in their approaches to facilitating collective action in digital transformation initiatives within healthcare settings.